A Survey of the Use Of Social Media among Undergraduate Student in the Faculties of Law in Universities Osun State Nigeria - IGBENEGHU, BRUNO IFAORUMHE; Johnson, Oluwadamilola A.; Osuji, Chioma N. (Edulib, 2021)
The study examined the awareness and use of social media platforms among undergraduate law students in universities in Osun State. It also investigated the extent to which  gender, age, level of study  and awareness of social media platforms influence the use of social media platforms among respondents. The study adopted a descriptive survey research design. The study population comprised undergraduate students in faculties of law in three selected universities in Osun state.  The instrument for data collection was the questionnaire. Five hundred and twenty seven (527) respondents participated in the study. Data were analysed using descriptive statistics, Pearson Product Moment Correlation and multiple Regression Analysis.   The results of the study revealed that respondents exhibited a low level of awareness and use of social media platforms. WhatsApp was found to be the most popular and utilised social media platform. The study also revealed that social media platforms were used mainly for online trading and seeking general knowledge about doing business. The study revealed that use of social media platforms had no significant relationship with gender (r = -.018, p 0.05), age (r = 0.011, p 0.05) and level of study ( r =  0.034, p 0.05), but had significant positive  relationship with awareness of social media platforms ( r = 0.234,  p 0.05). In addition, the study revealed that a combination of gender, age, level of study and awareness of social media platforms significantly influenced the use of social media platforms among respondents. (F = 7.507, df = 4: 522, p 0.05). Awareness of social media platforms (β = 0.237, t = 5.397, p 0.05) was found to be the only significant predictor variable in the use of social media platforms among respondents. It was concluded from the study that gender, age, level of study and the awareness of social media platforms significantly influenced the use of social media platforms among undergraduate law students in universities in Osun state, Nigeria. It was recommended that these factors be taken into account by university administrators when making policies on the use of social media in the university system.